Bears in the streets three journeys across a changing Russia - Dickey, Lisa (St. Martin's Press, 2017)
"Lisa Dickey traveled across the whole of Russia three times...in 1995, 2005 and 2015...making friends in eleven different cities, then coming back again and again to see how their lives had changed. Like the acclaimed British documentary series Seven Up!, she traces the ups and downs of ordinary people's lives, in the process painting a deeply nuanced portrait of modern Russia. From the caretakers of a lighthouse in Vladivostok, to the Jewish community of Birobidzhan, to a farmer in Buryatia, to a group of gay friends in Novosibirsk, to a wealthy 'New Russian' family in Chelyabinsk, to a rap star in Moscow, Dickey profiles a wide cross-section of people in one of the most fascinating, dynamic and important countries on Earth. Along the way, she explores dramatic changes in everything from technology to social norms, drinks copious amounts of vodka, and learns firsthand how the Russians really feel about Vladimir Putin. Including powerful photographs of people and places over time, and filled with wacky travel stories, unexpected twists, and keen insights, Bears in the Streets offers an unprecedented on-the-ground view of Russia today"...
Keywords: Dickey, Lisa -- Travel -- Russia (Federation); Geschichte 1995-2015; TRAVEL / Russia; HISTORY / Europe / Russia & the Former Soviet Union; TRAVEL / Essays & Travelogues; Social change -- Russia (Federation); Alltag; Europa; Russland; Russia (Federation) -- Description and travel; Russia (Federation) -- History, Local; Russia (Federation) -- Biography; Russia (Federation) -- Social conditions -- 1991-; Biografie